Zoonotic cutaneous leishmaniasis and Leishmania infection among Meriones shawi population in Setif Province, Algeria (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fellahi A, Djirar N, Cherief A, Boudrissa A, Eddaikra N. 2021. Zoonotic cutaneous leishmaniasis and Leishmania infection among Meriones shawi population in Setif Province, Algeria. Biodiversitas 22: 2547-2554. Zoonotic cutaneous leishmaniasis (ZCL) is the most endemic disease in Algeria. Leishmania major is the causative agent, and Gerbils Meriones shawi and Psammomys obesus are the main reservoir hosts. The Province of Setif in Algeria has become a very active focus for this zoonosis. Our study was carried out from January 2017 until January 2019 in ten representative stations of the study area, with an aim to identify the association between zoonosis and reservoir host species. Eighty-six (86) specimens of M. shawi and three (3) specimens of P. obesus were captured and determined. Superficial lesions were subjected to Giemsa stained smears. In addition, Livers and spleens were tested for Leishmania DNA using ITS1 PCR. The results showed the presence of M. shawi in almost all communities of Setif Province and the highest population with 50 specimens (58.13%) was in the center and south. The microscopic and molecular detection of Leishmania showed high infestation in most specimens of Meriones (32/86) with a rate of 37.20 %, however, no infestation in Psammomys has been detected. The PCA results showed a negative association between rainfall and ZCL cases; however, positive association was found between temperature and the human CL cases. Also, positive association was demonstrated between ZCL in south and center of Setif Province and Meriones captured. Our finding, confirm that M. shawi is the principal reservoir host (76.78%) of the ZCL in Setif Province, since P. obesus was nearly absent (2.67%).
Keywords: DNA Extraction Leishmania, Meriones Shawi, Reservoir Host, Rodent, Zoonotic Cutaneous Leishmaniasis.